2016
DOI: 10.1080/02770903.2016.1218015
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a school-based asthma educational program

Abstract: School-based asthma educational programs can significantly improve teachers' knowledge of asthma and their competence in providing asthma-related first aid interventions during emergencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was due to their history with such children. Moreover, the study suggested that educational programs can be effective in terms of training teachers and in enhancing their knowledge (Al Aloola et al, 2017). However, in Jordan, the primary school teachers are only responsible for managing the patients with asthma because there are no school nurses, available in Jordanian schools (Kawafha & Tawalbeh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was due to their history with such children. Moreover, the study suggested that educational programs can be effective in terms of training teachers and in enhancing their knowledge (Al Aloola et al, 2017). However, in Jordan, the primary school teachers are only responsible for managing the patients with asthma because there are no school nurses, available in Jordanian schools (Kawafha & Tawalbeh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness amongst teachers may create awareness amongst students 13 . School-based asthma educational programme for teachers can significantly improve teachers' knowledge of asthma and their competence in providing asthma-related first aid interventions during emergencies 14 . Awareness about asthma triggers, specifically environmental pollution, should be created amongst community leaders and policymakers.…”
mentioning
confidence: 99%